Strategi Inovatif Dalam Pengembangan Komunitas DKV Fisip Unija - Moh Nurul Hakim; Hidayat . (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2025)
Innovative strategies in developing the Visual Communication Design (DKV) community in the FISIP Wiraraja University environment. The approach used is descriptive qualitative with a case study method, through in-depth interviews, participatory observation, and analysis of community activity documentation. The results of the study indicate that the DKV community is in the phase of forming and strengthening its identity, with student initiatives as the main driver. Innovative strategies implemented include the use of social media (Instagram, TikTok, YouTube) to build a digital identity and disseminate educational content, internal training based on needs, and integration of user feedback in design development. Community activities also reflect a collaborative and user-centered design approach, such as the preparation of visual templates and digital portfolio catalogs. However, the community still faces challenges in the form of limited resources, non-standardized training structures, and lack of external collaboration. This study recommends strengthening level-based training, integrating social and technological issues into design practices, and developing cross-sector partnerships. The FISIP DKV community has great potential as an agent of social and cultural change if innovative strategies are implemented sustainably and adaptively to technological developments.